2017
DOI: 10.1186/s13756-017-0209-9
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of long term care facility patients with MDR-Gram-negatives during an Acinetobacter baumannii outbreak

Abstract: BackgroundWe aimed to determine the prevalence of colonization by multidrug-resistant Gram-negative bacteria including ESBL-producing enterobacteriaceae, carbapenem-resistant enterobacteriaceae, Pseudomonas aeruginosa and Acinetobacter baumannii at two wards caring long term for patients with disorder of consciousness at the Geriatric Health Centers Graz, Austria. During our study we detected two A. baumannii outbreaks.MethodsIn August 2015, we conducted a point-prevalence study. Inguinal and perianal swabs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Looking at neighbouring countries, data from LTCFs in Italy show that the prevalence of ESBL-producers and CPE is as high as 64% and 6%, respectively [71, 72]. A point prevalence study from 2015 performed in an Austrian LTCF reported a prevalence of 13% for ESBL, whereas no CPE were found [73]. In Germany, data from 2012 among nursing home residents showed a prevalence of 27% for ESBL, 9% for MRSA and 3% for VRE [74].…”
Section: Discussionmentioning
confidence: 99%
“…Looking at neighbouring countries, data from LTCFs in Italy show that the prevalence of ESBL-producers and CPE is as high as 64% and 6%, respectively [71, 72]. A point prevalence study from 2015 performed in an Austrian LTCF reported a prevalence of 13% for ESBL, whereas no CPE were found [73]. In Germany, data from 2012 among nursing home residents showed a prevalence of 27% for ESBL, 9% for MRSA and 3% for VRE [74].…”
Section: Discussionmentioning
confidence: 99%
“…After analysis of the data available, PUS patient was most probably the source of the IO. It appears that the transmission of Acinetobacter strains and the development of epidemic outbreaks in hospitals may also result from transferring patients between departments [12,58]. In the situation analyzed by us, the patient rotation in the department of vascular surgery and hospitalization of patients in different units, e.g., transferring patients from the ICU to the department of vascular surgery (PUS patient), resulted in contact between patients qualified for IO and IIO.…”
Section: Discussionmentioning
confidence: 99%
“…It is also generally accepted that A. baumannii clones do not demonstrate such great and rapid variability as other microorganisms causing hospital epidemics (MRSA, VRE) [12,59,60]. Epidemic outbreaks caused by the same epidemic clone of A. baumannii, which occurred in long intervals (of over several months), had been described before [12,61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, clinical observations by one of the authors (M.S.) suggested efficacy of Omnibiotic10 AAD ® in eliminating colonization by multidrug-resistant Acinteobacter baumannii isolates following an outbreak [ 24 ].…”
Section: Introductionmentioning
confidence: 99%